2018
DOI: 10.1159/000494896
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Candidate Genes for Mayer-Rokitansky-Küster-Hauser Syndrome Using Genomic Approaches

Abstract: Mayer-Rokitansky-Küster-Hauser (MRKH) syndrome is a disorder of sex development which affects 1 in 4,500 females and is characterized by agenesis of müllerian structures, including the uterus, cervix, and upper vagina. It can occur in isolation (type 1) or in conjunction with various anomalies (type 2), with a subset of these comprising müllerian, renal, and cervicothoracic abnormalities (MURCS) association. The genetic causes of MRKH have been investigated previously yielding limited results, with massive par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 35 publications
0
31
0
1
Order By: Relevance
“…Recently, Pan et al performed whole-genome sequencing (WGS) analysis of nine MRKH syndrome trios (patient and both parents) demonstrating the capacity of WGS in unbiased detection of de novo genomic variation [77]. Other recent studies also used NGS technology in genomic searches for genetic variation [24,64,78,79]. However, it remains a challenge to interpret the pathogenicity of these findings and investigations of larger cohorts will likely be needed in order to identify recurrent genetic variation.…”
Section: Embryology Etiology and Geneticsmentioning
confidence: 99%
“…Recently, Pan et al performed whole-genome sequencing (WGS) analysis of nine MRKH syndrome trios (patient and both parents) demonstrating the capacity of WGS in unbiased detection of de novo genomic variation [77]. Other recent studies also used NGS technology in genomic searches for genetic variation [24,64,78,79]. However, it remains a challenge to interpret the pathogenicity of these findings and investigations of larger cohorts will likely be needed in order to identify recurrent genetic variation.…”
Section: Embryology Etiology and Geneticsmentioning
confidence: 99%
“…The advent of the genome era of human genetics has seen a dramatic increase in the pace of gene discovery, especially for more common and recognizable syndromes. Yet many well‐characterized human malformation syndromes and associations remain unsolved despite extensive investigations (Boycott, Dyment, & Innes, 2018), including chromosome microarray analysis, exome sequencing, and deep sequencing of single genes to detect mosaic mutations (Backhouse et al, 2019; Hartsfield, 2007; Keppler‐Noreuil, Gorton, Foo, Yankowitz, & Keegan, 2007; Solomon, 2018; Solomon et al, 2013). Among these are several syndromes or associations reported to occur more frequently than expected in monozygotic discordant twins and other multiple births (Chen et al, 2018; Bartels et al, 2012; Wieczorek et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Each of these associations or syndromes share an early embryonic origin, no (or extremely rare) reports of familial recurrence (Backhouse et al, 2019;Chen et al, 2018;Solomon, 2018), and an excess of reported discordant twins and other multiple births (Bartels et al, 2012;Wieczorek et al, 2007). They share other common features as well.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…WES also found a rare homozygous variant in CDC42BPB in three sisters with septate uterus ( Luo et al, 2020 ). Backhouse et al (2019) used WES in combination with microarrays in patients with MRKH and found damaging variants of several genes: LRP10 , encoding a lipoprotein receptor; FRAS1 , encoding an extracellular matrix protein previously described as essential for metanephros organogenesis ( Pitera et al, 2008 ); RSPO4 , involved in the WNT pathway; NPHP3 , which was previously linked to kidney development ( Olbrich et al, 2003 ); DYNC2H1 , a cilium-related dynein; and NAALADL2 , which encodes an enzyme not yet linked to MDAs. This study also identified MKKS , the gene that triggers McKusick–Kaufman syndrome (OMIM 236700), presenting reproductive effects related to vaginal maldevelopment ( Backhouse et al, 2019 ).…”
Section: Technologies and Strategies To Investigate Mda Genetics And Genomicsmentioning
confidence: 99%